The Concept of A Marriage Agreement in the Compilation of Islamic Law - Haerunnisa Yunus; Rusli Rusli; Abidin Abidin (State Institute for Islamic Studies Palu, 2020)
The aim of this paper is to discusse the concept of a marriage agreement in the Compilation of Islamic Law. This study is literature review research with a qualitative methods. The data was gathered through content analysis and written material. Data analysis was analyzed using grounded theory approach and thematic building. The result of research shows basically, there is no difference between the Marriage Law and the Islamic Law Compilation regarding the marriage agreement. Second, the legal consequences of the marriage agreement made by each party—husband and wife, are binding. Therefore, if a violation occurs, each party can take legal action.